Centering Reliability and Evidence: Integrating Site Reliability Engineering Error Budget Governance with Evidence Based Practice Implementation Frameworks in Large Scale Digital Health Systems - Dr. Elias K. Brandner (Academic Reseach Library for International Journal of Computer Science & Information System, 2026)
The accelerating digitization of health care delivery, research, and administration has produced a paradoxical condition in which clinical systems are more information rich than at any point in history while simultaneously becoming more operationally fragile. Digital infrastructures that support electronic health records, clinical decision support, telemedicine platforms, and population health analytics are now mission critical to patient safety, institutional credibility, and regulatory compliance. Yet these infrastructures are routinely exposed to downtime, performance degradation, security incidents, and data integrity failures that threaten the very epistemic foundations of evidence based medicine. Within this context, site reliability engineering has emerged as a dominant paradigm for governing large scale software systems through quantifiable objectives, error budgets, and continuous improvement. At the same time, the health sciences have spent more than three decades refining evidence based practice frameworks to guide decision making, professional education, and organizational change. These two traditions have evolved largely in parallel, despite sharing a core concern with how knowledge, uncertainty, and risk are managed under real world conditions. Using a qualitative meta analytic methodology grounded in the interpretive synthesis of existing empirical and theoretical studies, the paper identifies recurring patterns that link error budget governance to professional behavior, organizational learning, and patient outcomes. The results demonstrate that reliability oriented metrics can function as powerful boundary objects that align clinical, managerial, and technical communities, while also revealing tensions when quantitative reliability targets conflict with qualitative judgments of care quality. The discussion elaborates these tensions in light of debates within evidence based practice about standardization, professional autonomy, and contextualization of knowledge. It further examines how error budgets can be misused as instruments of control or cost containment if detached from clinical values, echoing long standing critiques of technocratic implementations of evidence based medicine. By situating site reliability engineering within the broader epistemological and organizational debates of evidence based practice, this study provides a novel framework for understanding how digital health systems can be governed in a way that is both technically robust and clinically meaningful. The conclusion outlines implications for health care leaders, educators, and researchers, arguing that future progress in digital health will depend on the deliberate co design of reliability engineering practices and evidence based implementation strategies.